Low-thermal-conductivity ceramic rock plate and preparation method thereof
By adopting a double-layer glaze layer structure on the ceramic rock slab and using a low thermal conductivity system composed of specific raw materials, the problem of high thermal conductivity of the ceramic rock slabs resulting in a cool touch is solved, and the low thermal conductivity and high wear resistance of the ceramic rock slabs are achieved , anti-fouling performance, while improving the delicateness and smoothness of the glaze surface.
Patent Information
- Application Number
- CN202411661743.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
Due to its high thermal conductivity, ceramic rock slabs will feel cold when touched, which will affect the user's comfortable experience.
Using a double-layer glaze layer structure, the first glaze layer consists of silicon micropowder, wollastonite, nanomontmorillonite, glass fiber, potassium feldspar, sodium feldspar, calcite and boron fuse powder, and the second glaze layer is It consists of eloite, montmorillonite, mica, peraceous stone, celite, wollastonite and barium strontium fuse powder. Through the reasonable combination and hierarchy of these raw materials, the thermal conductivity of ceramic rock slabs is reduced. .
It effectively reduces the thermal conductivity of ceramic rock slabs, makes them feel warm and cool, while improving the texture and visual effect of the glaze.
Smart Images

Figure BDA0005143576760000031 
Figure BDA0005143576760000032 
Figure BDA0005143576760000041
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of building ceramics, and in particular relates to a low thermal conductivity ceramic rock plate and a preparation method thereof. Background Art
[0002] As a high-performance building decoration material, ceramic rock board has the advantages of good strength, hardness, wear resistance, antifouling, acid and alkali resistance and impermeability, and is widely used in indoor and outdoor walls and floors. At the same time, as a kind of ceramic material, ceramic rock board, like most ceramic materials, has high thermal conductivity. When it comes into contact with the air, it will quickly adjust its own temperature to the temperature of the surrounding environment. Therefore, especially when the temperature is low, the surface temperature of ceramic rock board is lower than that of other materials such as wood or fabric. And because of the good thermal conductivity of ceramic rock board, it is also very sensitive to temperature changes. When the outside temperature drops, the temperature of ceramic rock board will drop rapidly, so it will feel cold when touched. In addition, ceramic rock board itself has a low heat storage capacity. Compared with other materials such as wood or fabric, ceramic rock board will not store a lot of heat like them. Therefore, when touched, the surface temperature of ceramic rock board is low, and there will be a cool touch, which affects the user's comfort experience.
[0003] Therefore, it is necessary to develop a ceramic rock plate with low thermal conductivity so that it is no longer cold when touching the film, but has a warm touch. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a low thermal conductivity ceramic rock plate and a preparation method thereof, wherein the ceramic rock plate has a low thermal conductivity coefficient and good wear resistance and antifouling properties.
[0005] In order to solve the above technical problems, the first aspect of the present invention provides a ceramic rock plate, which comprises, from bottom to top, a body, a first surface glaze layer, a second surface glaze layer, a pattern layer and a protective glaze layer;
[0006] The raw material components of the first glaze layer include: silicon micropowder, wollastonite, nano-montmorillonite, glass fiber, potassium feldspar, sodium feldspar, calcite and boron frit powder;
[0007] The raw material components of the second glaze layer include: halloysite, montmorillonite, hydromica, pearlite, dickite, nepheline, wollastonite and barium strontium frit powder.
[0008] The present invention sequentially arranges the first glaze layer and the second glaze layer on the surface of the body, and optimizes and reasonably compound the components of each layer, so that the two glaze layers have a lower thermal conductivity, which effectively isolates the coolness of the body and reduces the conduction of heat, thereby making the ceramic rock plate have a suitable touch temperature and reducing the cold feeling. The construction of the double-layer glaze layer is not only conducive to reducing the thermal conductivity of the ceramic rock plate, but also conducive to improving the texture and visual effect of the glaze surface.
[0009] Specifically, among the raw material components of the first glaze layer, silicon powder has low thermal conductivity, which can form a relatively stable structure in the glaze system and hinder the transfer of heat; its fine particle size increases the interface of phonon scattering, making phonons more easily scattered during the transfer process, thereby reducing thermal conductivity. Wollastonite is a single-chain silicate mineral, the main component of which is Ca3Si3O9. Its crystal structure and chemical composition enable it to effectively reduce the conduction of heat. When heat is transferred to the area where wollastonite powder is located, its structure can block and disperse the heat to a certain extent, reduce the transfer efficiency of heat flow, and form an insulating structural framework in the glaze. Nano-montmorillonite powder has a layered structure, and the interaction between layers can hinder heat transfer; when heat tries to pass through the glaze, the layered structure of nano-montmorillonite powder will make the propagation path of phonons tortuous, increase the probability of phonon scattering, and thus reduce thermal conductivity. The thermal conductivity of glass fiber itself is low, and it can form a disordered network structure in the glaze; this network structure can increase the path length of heat transfer, so that the heat needs to pass through more obstacles during the transfer process, thereby reducing the efficiency of heat conduction; at the same time, glass fiber can also interact with other raw materials to further optimize the microstructure of the glaze and enhance the thermal insulation effect. Potassium feldspar and sodium feldspar cooperate with other low thermal conductivity raw materials to adjust the overall performance of the glaze; they can work together with other low thermal conductivity raw materials to jointly reduce the thermal conductivity of the glaze while ensuring the basic physical and chemical properties of the glaze. Calcite can interact with other raw materials, change the microstructure of the glaze, increase the resistance to heat transfer, and thus help reduce the thermal conductivity of the glaze. Boron frit powder can fill and connect other raw materials in the glaze, and together with other low thermal conductivity raw materials, construct a continuous low thermal conductivity system to reduce the heat conduction path in the glaze, thereby achieving the effect of low thermal conductivity. Therefore, the raw material components of the first glaze layer interact with each other to jointly construct a low thermal conductivity system, which can effectively reduce the thermal conductivity of the ceramic rock plate.
[0010] Among the raw material components of the second glaze layer, halloysite powder has good plasticity and adhesion, which helps to improve the molding performance of the glaze, make the glaze surface more uniform, and enhance the delicate texture of the glaze. Montmorillonite powder has excellent adsorption and ion exchange properties, which can affect the fusibility and transparency of the glaze; it helps to adjust the opacity of the glaze, so that the glaze surface presents a soft translucent effect with texture. Hydromica powder has a good flaky structure, which can improve the covering power and wear resistance of the glaze; it is beneficial to enhance the gloss and stain resistance of the glaze surface, making the glaze surface smoother and more delicate. Pearl stone powder has high whiteness and transparency, which helps to improve the overall texture of the glaze; it makes the glaze surface present a whiter and more translucent visual effect. Dickite powder has good high temperature resistance and chemical stability, which can improve the sintering performance of the glaze; it can ensure that the glaze can form a uniform and dense glaze surface at high temperature and improve the mechanical properties of the product. Nepheline powder is rich in alkali metal oxides such as potassium and sodium, which helps to lower the melting point of the glaze and improve its fluidity; it makes the glaze easier to flow during the firing process, forming a uniform and smooth glaze surface. Wollastonite powder has high whiteness and good mechanical strength, which can improve the wear resistance and glossiness of the glaze; and enhance the hardness and scratch resistance of the glaze surface. Barium strontium frit powder can lower the melting point of the glaze, improve its opacity and glossiness; it helps to form a more delicate and smooth glaze surface, while increasing the firing temperature range of the product and reducing production costs. Therefore, the raw material components of the second glaze layer interact with each other, which promotes the low thermal conductivity of the first glaze layer while helping to improve the texture effect of the glaze surface, so that the glaze presents a delicate, smooth, translucent and shiny appearance after firing.
[0011] In some embodiments of the present invention, the raw material components of the first glaze layer include, by weight:
[0012]
[0013] In some embodiments of the present invention, the chemical composition of the boron frit powder includes, by weight percentage: SiO2 60-68%, Al2O3 6-12%, Fe2O3 0.01-0.03%, TiO2 0.01-0.03%, CaO 5-10%, MgO 1-4%, K2O 3-5%, Na2O 2-4%, ZrO2 0.5-1%, ZnO 2-5%, B2O3 8-14%, BaO 0.5-1%, and loss on ignition 4-8%.
[0014] In some embodiments of the present invention, the raw material components of the first glaze layer further include, by weight: 5-15 parts of a flow rate regulator and 0.08-0.15 parts of a dispersion regulator.
[0015] Specifically, the flow rate regulator is mainly used to adjust the flow rate of the glaze so that it can evenly cover the surface of the body during the glazing process. The dispersion regulator is mainly used to improve the dispersion of particles in the glaze and prevent the particles from agglomerating, thereby improving the stability and uniformity of the glaze.
[0016] In some embodiments of the present invention, the flow rate regulator is selected from at least one of polyethylene glycol (PEG), polyacrylate, polyvinyl alcohol (PVA), polystyrene oligomers, polymethyl methacrylate oligomers (PMMA), polyacrylamide oligomers, and surfactants.
[0017] In some embodiments of the present invention, the surfactant is selected from at least one of sodium dodecyl sulfate (SDS), polyoxyethylene ether (POE), and Gemini surfactant.
[0018] In some embodiments of the present invention, the dispersion regulator is selected from at least one of sodium polyacrylate, sodium hexametaphosphate, and sodium tripolyphosphate.
[0019] In some embodiments of the present invention, the raw material components of the second glaze layer include, by weight:
[0020]
[0021]
[0022] In some embodiments of the present invention, the chemical composition of the barium strontium frit powder includes, by weight percentage: SiO2 50-58%, Al2O3 5-15%, BaO 15-20%, SrO 6-10%, K2O 1-3%, Na2O 1-3%, CaO 1-4%, and loss on ignition 2-6%.
[0023] In some embodiments of the present invention, the raw material components of the second glaze layer further include: 5-15 parts of flow rate regulator and 0.08-0.15 parts of dispersion regulator by weight. The raw materials of the flow rate regulator and dispersion regulator in the raw material components of the second glaze layer are the same as those of the first glaze layer.
[0024] In some embodiments of the present invention, the raw material components of the protective glaze layer include, by weight:
[0025]
[0026] Specifically, among the raw material components of the protective glaze layer, potassium feldspar and sodium feldspar can cooperate with other raw materials in the protective glaze to adjust the overall performance of the glaze; at the same time, their crystal structure and chemical composition can affect the propagation path of phonons in the glaze system, increase phonon scattering, and thus reduce thermal conductivity to a certain extent. Barium carbonate and strontium carbonate will decompose at high temperatures to produce gas, forming a tiny pore structure in the glaze; these pores can effectively hinder the transfer of heat because the thermal conductivity of gas is much lower than that of solid materials; the pores increase the path length of heat transfer, making phonons more easily scattered during the transfer process, thereby reducing the thermal conductivity of the glaze. Burnt talc has a layered structure that can interfere with the conduction of heat; when heat tries to pass through the glaze, the layered structure of burned talc will make the propagation path of phonons tortuous, increase the probability of phonon scattering, and reduce thermal conductivity. Zinc oxide plays a role in refining grains in glazes, making the microstructure of glazes more dense and uniform; uniform and dense microstructures can reduce the channels for heat conduction and increase phonon scattering, which is beneficial to reducing the thermal conductivity of glazes. Washed kaolin and calcined kaolin have a flaky structure, which can increase the phonon scattering interface in glazes; at the same time, their chemical composition and physical properties can adjust the viscosity and sintering properties of glazes, so that the glazes form a microstructure that is beneficial to reducing thermal conductivity during sintering. The crystal structure and chemical composition of calcite and dolomite can change the microstructure in glazes and increase the resistance to heat transfer; at the same time, they interact with other raw materials to form a complex microstructure that hinders heat conduction. Calcined alumina has high hardness and good chemical stability, and can form a stable structural framework in glazes; this structural framework can increase the path length of heat transfer, and its own thermal conductivity is relatively low, which helps to reduce the thermal conductivity of glazes. Barium zinc frit can fill and connect other raw materials in the glaze. At the same time, its own thermal conductivity is relatively low. It can build a continuous low thermal conductivity system with other low thermal conductivity raw materials to reduce the heat conduction path in the glaze, thereby achieving the effect of low thermal conductivity. Therefore, the various raw material components of the protective glaze layer interact with each other, which not only provides a low thermal conductivity effect, but also helps to enhance the wear resistance and stain resistance of the glaze surface and extend the service life of the product.
[0027] At the same time, the first glaze layer, the second glaze layer and the protective glaze layer promote each other. The two-layer glaze mainly controls the formula composition of the glaze to reduce the thermal conductivity of the glaze and improve the texture of the glaze; while the protective glaze fills the microscopic pores of the glaze on the basis of the low thermal conductivity glaze layer, reduces the heat transfer channel, and further reduces the thermal conductivity of the ceramic rock plate as a whole and provides additional protection for the product.
[0028] In some embodiments of the present invention, the initial melting temperature of the protective glaze is 1030-1080°C, and the initial melting temperatures of the first glaze layer and the second glaze layer are 60-90°C higher than the initial melting temperature of the protective glaze.
[0029] Specifically, the present invention controls the initial melting temperatures of the surface glaze layer (including the first surface glaze layer and the second surface glaze layer) and the protective glaze layer, and makes a certain temperature difference between the initial melting temperature of the surface glaze layer and the initial melting temperature of the protective glaze, mainly based on the following three reasons:
[0030] First, ensure the formation of a layered structure. When the top glaze and protective glaze are applied to the surface of the body in sequence, the existence of the initial melting temperature difference can ensure that the protective glaze layer begins to melt before the top glaze layer during the firing process. This allows the protective glaze layer to better fill the microscopic pores of the top glaze and some tiny defects on the surface of the brick body after melting, forming a layered structure. This layered structure helps to further reduce the channels for heat transfer, because the structural and compositional differences between different layers can increase phonon scattering and improve the thermal insulation effect.
[0031] Second, avoid mutual interference. If the initial melting temperatures of the surface glaze layer and the protective glaze layer are similar or the same, they will melt and mix together during the firing process, and cannot form an ideal layered structure. This will not only affect the thermal conductivity of the final product, but also cause glaze quality problems such as uneven glaze surface and uneven color. By controlling the initial melting temperature difference, the surface glaze layer and the protective glaze layer can be melted and solidified in the expected order during the firing process, each playing its due role and avoiding mutual interference.
[0032] Third, optimize the physical and chemical properties. Reasonable control of the initial melting temperature difference between the surface glaze layer and the protective glaze layer can optimize the overall performance of the ceramic rock plate, which is beneficial to improving the product's wear resistance and stain resistance. After the surface glaze layer melts at a suitable temperature, it can better realize its function of reducing thermal conductivity and providing a suitable hand-feeling temperature. This temperature difference control enables the surface glaze layer and the protective glaze layer to work together, while ensuring the product's low thermal conductivity, it also improves other performance aspects, such as wear resistance and anti-fouling performance.
[0033] In some embodiments of the present invention, the chemical composition of the barium zinc frit powder includes, by weight percentage: SiO2 45-50%, Al2O3 15-20%, Fe2O3 0.1-0.2%, TiO2 0.1-0.2%, CaO 3-8%, MgO 1-3%, K2O 3-6%, Na2O 1-4%, P2O5 0.1-0.3%, SrO 4-6%, ZrO2 0.01-0.05%, BaO 3-5%, ZnO 5-10%, PbO0.02-0.06%, and loss on ignition 0.2-0.5%.
[0034] In some embodiments of the present invention, the raw material components of the green body include, by weight: 12-16 parts of sodium feldspar, 24-27 parts of potassium feldspar, 26-30 parts of ball clay, 8-12 parts of bentonite, 3-6 parts of high-temperature sand, 11-15 parts of medium-temperature sand, and 4-6 parts of calcined talc. The chemical composition of the green body includes, by weight percentage: SiO2 65.21-68.63%, Al2O3 18.63-22.05%, Fe2O3 0.08-0.25%, TiO2 0.05-0.09%, CaO 0.3-0.6%, MgO 1.93-2.35%, K2O3.23-3.88%, Na2O2.65-3.17%, and ignition loss 4.5-5.0%. The present invention has no special requirements for the raw material components of the green body, and ordinary ceramic rock plate green bodies can be used.
[0035] A second aspect of the present invention provides a method for preparing a ceramic rock plate, comprising the following steps:
[0036] The first glaze, the second glaze, the spray-printed pattern and the protective glaze are sequentially applied on the blank to form the first glaze layer, the second glaze layer, the pattern layer and the protective glaze layer in sequence. After drying, the blank is fired in a kiln to obtain the ceramic rock slab.
[0037] In some embodiments of the present invention, the maximum sintering temperature is 1200-1220°C.
[0038] In some embodiments of the present invention, the firing cycle is 40-60 minutes.
[0039] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0040] (1) The present invention sequentially arranges a first glaze layer and a second glaze layer on the surface of the body, wherein: the raw material components of the first glaze layer include silicon micropowder, wollastonite, nano-montmorillonite, glass fiber, potassium feldspar, sodium feldspar, calcite and boron frit powder, and the raw material components interact with each other to jointly construct a low thermal conductivity system, which effectively reduces the thermal conductivity of the ceramic rock plate. The raw material components of the second glaze layer include halloysite, montmorillonite, hydromica, perlite, dickite, nepheline, wollastonite and barium strontium frit powder, and the raw material components interact with each other, while promoting the low thermal conductivity of the first glaze layer, the texture effect of the glaze is improved, so that the glaze presents a delicate, smooth, translucent and glossy appearance after firing. Both the first glaze layer and the second glaze layer have a low thermal conductivity coefficient, which can effectively isolate the coolness of the body, reduce the conduction of heat, and make the ceramic rock plate have a suitable touch temperature and reduce the cold feeling.
[0041] (2) The ceramic rock slab prepared by the present invention has low thermal conductivity and high wear resistance and anti-fouling properties, achieving a thermal conductivity of 0.50-0.55 W / m·K, wear resistance of up to level 5, and no residual stains in the anti-fouling test; and the glaze surface is smooth, delicate, and rich in texture. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0043] Example 1
[0044] A ceramic rock slab comprises, from bottom to top, a body, a first glaze layer, a second glaze layer, a pattern layer and a protective glaze layer.
[0045] The raw material components of the green body include, by weight: 12 parts of albite, 24 parts of potassium feldspar, 26 parts of ball clay, 8 parts of bentonite, 3 parts of high-temperature sand, 11 parts of medium-temperature sand, and 4 parts of calcined talc. The chemical composition of the green body includes, by weight percentage: SiO2 68.63%, Al2O3 18.63%, Fe2O3 0.08%, TiO2 0.05%, CaO 0.3%, MgO 1.93%, K2O3.23%, Na2O 2.65%, and ignition loss 4.5%.
[0046] The raw material components of the first glaze layer include, by weight:
[0047]
[0048] Among them: the initial melting temperature of the first glaze layer is 1130°C, the flow rate regulator includes 3.3 parts of polyethylene glycol, 3.3 parts of polystyrene oligomer, and 3.3 parts of sodium dodecyl sulfate; the dispersion regulator includes 0.06 parts of sodium polyacrylate and 0.03 parts of sodium hexametaphosphate; the chemical composition of the boron frit powder, by weight percentage, includes: SiO2 60%, Al2O3 8%, Fe2O3 0.01%, TiO20.01%, CaO 5.5%, MgO 1.75%, K2O 4%, Na2O 1.85%, ZrO2 0.7%, ZnO 3.5%, B2O38%, BaO 0.75%, and loss on ignition 5.93%.
[0049] The raw material components of the second glaze layer include, by weight:
[0050]
[0051]
[0052] Among them: the initial melting temperature of the second glaze layer is 1130°C, the flow rate regulator includes 3.3 parts of polyethylene glycol, 3.3 parts of polystyrene oligomer, and 3.3 parts of sodium dodecyl sulfate; the dispersion regulator includes 0.06 parts of sodium polyacrylate and 0.03 parts of sodium hexametaphosphate; the chemical composition of the barium strontium frit powder includes, by weight percentage: SiO2 54.28%, Al2O3 10.06%, BaO17.92%, SrO 8.01%, K2O 1.95%, Na2O 1.90%, CaO 2.09%, and loss on ignition 3.79%.
[0053] The raw material components of the protective glaze layer include, by weight:
[0054]
[0055] Among them: the initial melting temperature of the protective glaze layer is 1055℃; the chemical composition of the barium zinc frit powder includes, by weight percentage: SiO2 49.5%, Al2O3 19.5%, Fe2O3 0.12%, TiO2 0.1%, CaO 4.8%, MgO 1.52%, K2O4.5%, Na2O 2.5%, P2O5 0.2%, SrO 5.2%, ZrO2 0.02%, BaO 4.2%, ZnO 7.5%, PbO0.04%, and loss on ignition 0.3%.
[0056] A method for preparing a ceramic rock plate comprises the following steps:
[0057] (1) weighing raw materials for preparing the green body according to the mass ratio, ball milling to obtain green body slurry, removing iron, spray granulation, aging, and pressing to obtain the green body;
[0058] (2) weighing the raw materials for preparing the first glaze layer, the second glaze layer and the protective glaze layer according to the mass ratio, wet ball milling, sieving and iron removal, and obtaining glaze slurries with a fineness of 0.4 wt% of the residue on a 325-mesh sieve, which are the first glaze, the second glaze and the protective glaze (specific gravity is 1.33);
[0059] (3) The first glaze and the second glaze prepared in step (2) are sequentially applied on the surface of the blank prepared in step (1), and then inkjet printing is performed using an inkjet printing machine, and finally a protective glaze (the glaze amount is 160 g / m 2) to sequentially form a first glaze layer, a second glaze layer, a pattern layer and a protective glaze layer. After drying, the glaze layer is fired at 1200°C for 40 minutes to obtain the ceramic rock slab of this embodiment.
[0060] Example 2
[0061] A ceramic rock slab comprises, from bottom to top, a body, a first glaze layer, a second glaze layer, a pattern layer and a protective glaze layer.
[0062] The raw material components of the green body include, by weight: 14 parts of sodium feldspar, 25 parts of potassium feldspar, 28 parts of ball clay, 10 parts of bentonite, 4 parts of high-temperature sand, 13 parts of medium-temperature sand, and 5 parts of calcined talc. The chemical composition of the green body includes, by weight percentage: SiO2 68.22%, Al2O3 20.34%, Fe2O3 0.16%, TiO2 0.07%, CaO 0.45%, MgO 2.14%, K2O3.56%, Na2O 2.91%, and ignition loss 4.75%.
[0063] The raw material components of the first glaze layer include, by weight:
[0064]
[0065] Among them: the initial melting temperature of the first glaze layer is 1090°C, the flow rate regulator includes 3 parts of polyethylene glycol, 3 parts of polystyrene oligomer, and 4 parts of sodium dodecyl sulfate; the dispersion regulator includes 0.06 parts of sodium polyacrylate and 0.04 parts of sodium hexametaphosphate; the chemical composition of the boron frit powder, by weight percentage, includes: SiO2 60%, Al2O3 8%, Fe2O3 0.01%, TiO20.01%, CaO 5.5%, MgO 1.75%, K2O 4%, Na2O 1.85%, ZrO2 0.7%, ZnO 3.5%, B2O3 8%, BaO 0.75%, and loss on ignition 5.93%.
[0066] The raw material components of the second glaze layer include, by weight:
[0067]
[0068]
[0069] Among them: the initial melting temperature of the second glaze layer is 1090°C, the flow rate regulator includes 3 parts of polyethylene glycol, 3 parts of polystyrene oligomer, and 4 parts of sodium dodecyl sulfate; the dispersion regulator includes 0.06 parts of sodium polyacrylate and 0.04 parts of sodium hexametaphosphate; the chemical composition of the barium strontium frit powder, by weight percentage, includes: SiO2 54.28%, Al2O3 10.06%, BaO17.92%, SrO 8.01%, K2O 1.95%, Na2O 1.90%, CaO 2.09%, and loss on ignition 3.79%.
[0070] The raw material components of the protective glaze layer include, by weight:
[0071]
[0072] Among them: the initial melting temperature of the protective glaze layer is 1030℃; the chemical composition of the barium zinc frit powder includes, by weight percentage: SiO2 49.5%, Al2O3 19.5%, Fe2O3 0.12%, TiO2 0.1%, CaO 4.8%, MgO 1.52%, K2O4.5%, Na2O 2.5%, P2O5 0.2%, SrO 5.2%, ZrO2 0.02%, BaO 4.2%, ZnO 7.5%, PbO0.04%, and loss on ignition 0.3%.
[0073] A method for preparing a ceramic rock plate comprises the following steps:
[0074] (1) weighing raw materials for preparing the green body according to the mass ratio, ball milling to obtain green body slurry, removing iron, spray granulation, aging, and pressing to obtain the green body;
[0075] (2) weighing the raw materials for preparing the first glaze layer, the second glaze layer and the protective glaze layer according to the mass ratio, wet ball milling, sieving and iron removal, and obtaining glaze slurries with a fineness of 0.4 wt% of the residue on a 325-mesh sieve, which are the first glaze, the second glaze and the protective glaze (specific gravity is 1.34);
[0076] (3) The first glaze and the second glaze prepared in step (2) are sequentially applied on the surface of the blank prepared in step (1), and then inkjet printing is performed using an inkjet printing machine, and finally a protective glaze (the glaze amount is 170 g / m 2 ) to sequentially form a first glaze layer, a second glaze layer, a pattern layer and a protective glaze layer. After drying, the glaze layer is fired at 1210°C for 50 minutes to obtain the ceramic rock slab of this embodiment.
[0077] Example 3
[0078] A ceramic rock slab comprises, from bottom to top, a body, a first glaze layer, a second glaze layer, a pattern layer and a protective glaze layer.
[0079] The raw material components of the green body include, by weight: 16 parts of sodium feldspar, 27 parts of potassium feldspar, 30 parts of ball clay, 12 parts of bentonite, 6 parts of high-temperature sand, 15 parts of medium-temperature sand, and 6 parts of calcined talc. The chemical composition of the green body includes, by weight percentage: SiO2 65.62%, Al2O3 20.34%, Fe2O3 0.16%, TiO2 0.07, CaO 0.45%, MgO 2.14%, K2O3.56%, Na2O 2.91%, and ignition loss 4.75%.
[0080] The raw material components of the first glaze layer include, by weight:
[0081]
[0082] Among them: the initial melting temperature of the first glaze layer is 1160℃, the flow rate regulator includes 5 parts of polyethylene glycol, 5 parts of polystyrene oligomer, and 5 parts of sodium dodecyl sulfate; the dispersion regulator includes 0.1 part of sodium polyacrylate and 0.05 part of sodium hexametaphosphate; the chemical composition of the boron frit powder, by weight percentage, includes: SiO2 60%, Al2O3 8%, Fe2O3 0.01%, TiO20.01%, CaO 5.5%, MgO 1.75%, K2O 4%, Na2O 1.85%, ZrO2 0.7%, ZnO 3.5%, B2O3 8%, BaO 0.75%, and loss on ignition 5.93%.
[0083] The raw material components of the second glaze layer include, by weight:
[0084]
[0085]
[0086] Among them: the initial melting temperature of the second glaze layer is 1170℃, the flow rate regulator includes 5 parts of polyethylene glycol, 5 parts of polystyrene oligomer, and 5 parts of sodium dodecyl sulfate; the dispersion regulator includes 0.1 parts of sodium polyacrylate and 0.05 parts of sodium hexametaphosphate; the chemical composition of the barium strontium frit powder includes, by weight percentage: SiO2 54.28%, Al2O3 10.06%, BaO 17.92%, SrO8.01%, K2O 1.95%, Na2O 1.90%, CaO 2.09%, and loss on ignition 3.79%.
[0087] The raw material components of the protective glaze layer include, by weight:
[0088]
[0089] Among them: the initial melting temperature of the protective glaze layer is 1080℃; the chemical composition of the barium zinc frit powder includes, by weight percentage: SiO2 49.5%, Al2O3 19.5%, Fe2O3 0.12%, TiO2 0.1%, CaO 4.8%, MgO 1.52%, K2O4.5%, Na2O 2.5%, P2O5 0.2%, SrO 5.2%, ZrO2 0.02%, BaO 4.2%, ZnO 7.5%, PbO0.04%, and loss on ignition 0.3%.
[0090] A method for preparing a ceramic rock plate comprises the following steps:
[0091] (1) weighing raw materials for preparing the green body according to the mass ratio, ball milling to obtain green body slurry, removing iron, spray granulation, aging, and pressing to obtain the green body;
[0092] (2) weighing the raw materials for preparing the first glaze layer, the second glaze layer and the protective glaze layer according to the mass ratio, wet ball milling, sieving and iron removal, and obtaining glaze slurries with a fineness of 0.4 wt% of the residue on a 325-mesh sieve, which are the first glaze, the second glaze and the protective glaze (specific gravity is 1.35);
[0093] (3) The first glaze and the second glaze prepared in step (2) are sequentially applied on the surface of the blank prepared in step (1), and then inkjet printing is performed using an inkjet printing machine, and finally a protective glaze (the glaze amount is 180 g / m 2 ), forming a first glaze layer, a second glaze layer, a pattern layer and a protective glaze layer in sequence, and after drying, firing at 1220°C for 60 minutes to obtain the ceramic rock slab of this embodiment.
[0094] Comparative Example 1
[0095] The only difference between Comparative Example 1 and Example 1 is that the ceramic rock slab of Comparative Example 1 does not contain a second glaze layer, that is, it includes a body, a first glaze layer, a pattern layer and a protective glaze layer from bottom to top.
[0096] Comparative Example 2
[0097] The only difference between Comparative Example 2 and Example 1 is that the ceramic rock slab of Comparative Example 2 does not contain the first surface glaze layer, that is, it includes a body, a second surface glaze layer, a pattern layer and a protective glaze layer from bottom to top.
[0098] Comparative Example 3
[0099] The difference between Comparative Example 3 and Example 1 is that the ceramic rock plate of Comparative Example 3 uses a common glaze layer to replace the first and second glaze layers of Example 1, that is, it includes a body, a common glaze layer, a pattern layer and a protective glaze layer from bottom to top. The raw material components of the common glaze layer include, by weight: 30 parts of kaolin, 20 parts of quartz, 30 parts of feldspar, 10 parts of calcite, 5 parts of zinc oxide, and 5 parts of barium carbonate.
[0100] Comparative Example 4
[0101] The difference between Comparative Example 4 and Example 1 is that the ceramic rock plate of Comparative Example 4 uses a common protective glaze layer instead of the protective glaze layer of Example 1, that is, from bottom to top, it includes a body, a first surface glaze layer, a second surface glaze layer, a pattern layer and a common protective glaze layer. The raw material components of the common protective glaze layer include, by weight: 25 parts of potassium feldspar, 20 parts of sodium feldspar, 15 parts of quartz, 10 parts of kaolin, 10 parts of calcium carbonate, 5 parts of magnesium carbonate, and 5 parts of zinc oxide.
[0102] Comparative Example 5
[0103] The only difference between Comparative Example 5 and Example 1 is that the initial melting temperature of the protective glaze layer of the ceramic rock slab of Comparative Example 5 is the same as the initial melting temperatures of the first glaze layer and the second glaze layer, both of which are 1130°C.
[0104] Performance Testing
[0105] The ceramic rock plate samples prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-5 were subjected to performance tests, and the quality of their glaze surfaces was observed. Among them: the thermal conductivity was tested according to ASTM E1461-13 using the laser flash method (LFA), and the sample size was 12.7 mm in diameter and 2 mm in thickness; the wear resistance was GB / T 3810.7-2016 "Test Methods for Ceramic Tiles - Part 7: Determination of Surface Wear Resistance of Glazed Tiles", and the wear resistance was divided into 0-5 levels, with 0 indicating the worst wear resistance and 5 indicating the best wear resistance. The greater the number of revolutions, the better the wear resistance. The anti-fouling performance was tested according to ISO 10545-14:2015 using the method of smearing and cleaning, and the sample size was length × width = 100 mm × 100 mm. The anti-fouling performance ranged from best to worst, and they were no residual stains, slight residual stains, obvious residual stains, and severe residual stains. The test results are shown in Table 1.
[0106] Table 1:
[0107]
[0108] It can be seen from Table 1 that the ceramic rock slabs prepared in Examples 1-3 have a low thermal conductivity, which can effectively isolate the coolness of the green body and reduce the conduction of heat, so that the ceramic rock slabs have a suitable touch temperature and reduce the cold feeling; at the same time, they have excellent wear resistance and anti-fouling properties, and the glaze is smooth, delicate and rich in texture.
[0109] Compared with Example 1, Comparative Example 1 and Comparative Example 2 do not contain the second glaze layer and the first glaze respectively, which not only leads to an increase in the thermal conductivity of the ceramic rock plate and an increase in the coldness of the brick body; the wear resistance and anti-fouling properties of the glaze also decrease to varying degrees, and the glaze surface is rough, not delicate and smooth enough, and the texture is poor.
[0110] Compared with Example 1, Comparative Example 3 uses an ordinary glaze layer to replace the first glaze layer and the second glaze layer of Example 1. Since the ordinary glaze layer fails to effectively construct a low thermal conductivity system, the thermal conductivity coefficient is relatively high. At the same time, the ordinary glaze layer has a significant adverse effect on the wear resistance, stain resistance and glaze quality of the glaze layer, resulting in a significant decrease in various performances.
[0111] Compared with Example 1, Comparative Example 4 uses a common protective glaze layer to replace the protective glaze layer of Example 1. The common protective glaze layer cannot effectively reduce the thermal conductivity of the brick body, and its wear resistance, antifouling property and glaze quality are all inferior to those of Example 1.
[0112] Compared with Example 1, the protective glaze layer, the first glaze layer and the second glaze layer of Example 5 have the same initial melting temperature. During the firing process, the protective glaze layer, the first glaze layer and the second glaze layer are melted and mixed together at the same time, and an ideal layered structure cannot be formed, resulting in an increase in the thermal conductivity of the brick body, and a decrease in the wear resistance and quality of the glaze.
[0113] In summary, the present invention effectively reduces the thermal conductivity of the ceramic rock plate, improves its wear resistance and stain resistance, and the glaze surface is delicate, smooth, and rich in texture through the combination of a specific first glaze layer, a second glaze layer, and a protective glaze layer. Any change in the product structure or component will lead to a decrease in product performance or glaze quality. The present invention achieves a low thermal conductivity and high wear resistance and stain resistance by optimizing the structure, components, and initial melting temperature of each glaze layer, and the glaze surface is smooth, delicate, and rich in texture.
[0114] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A ceramic rock plate, characterized in that: From bottom to top, it includes a body, a first glaze layer, a second glaze layer, a pattern layer and a protective glaze layer; The raw material components of the first glaze layer include: silicon micropowder, wollastonite, nano-montmorillonite, glass fiber, potassium feldspar, sodium feldspar, calcite and boron frit powder; The raw material components of the second glaze layer include: halloysite, montmorillonite, hydromica, pearlite, dickite, nepheline, wollastonite and barium strontium frit powder.
2. The ceramic rock plate according to claim 1, characterized in that: The raw material components of the first glaze layer include, by weight:
3. The ceramic rock plate according to claim 2, characterized in that: The chemical composition of the boron frit powder includes, by weight percentage: SiO2 60-68%, Al2O3 6-12%, Fe2O3 0.01-0.03%, TiO2 0.01-0.03%, CaO 5-10%, MgO 1-4%, K2O 3-5%, Na2O 2-4%, ZrO2 0.5-1%, ZnO 2-5%, B2O3 8-14%, BaO 0.5-1%, and loss on ignition 4-8%; And / or, the raw material components of the first glaze layer further include, by weight: 5-15 parts of a flow rate regulator and 0.08-0.15 parts of a dispersion regulator.
4. The ceramic rock plate according to claim 1, characterized in that: The raw material components of the second glaze layer include, by weight:
5. The ceramic rock plate according to claim 4, characterized in that: The chemical composition of the barium strontium frit powder includes, by weight percentage: SiO2 50-58%, Al2O3 5-15%, BaO 15-20%, SrO 6-10%, K2O 1-3%, Na2O 1-3%, CaO 1-4%, and ignition loss 2-6%; And / or, the raw material components of the second glaze layer further include, by weight: 5-15 parts of a flow rate regulator and 0.08-0.15 parts of a dispersion regulator.
6. The ceramic rock plate according to claim 3 or 5, characterized in that: The flow rate regulator is selected from at least one of polyethylene glycol, polyacrylate, polyvinyl alcohol, polystyrene oligomer, polymethyl methacrylate oligomer, polyacrylamide oligomer and surfactant; And / or, the dispersion regulator is selected from at least one of sodium polyacrylate, sodium hexametaphosphate and sodium tripolyphosphate.
7. The ceramic rock plate according to claim 1, characterized in that: The raw material components of the protective glaze layer include, by weight:
8. The ceramic rock plate according to claim 7, characterized in that: The chemical composition of the barium zinc frit powder includes, by weight percentage, SiO2 45-50%, Al2O3 15-20%, Fe2O3 0.1-0.2%, TiO2 0.1-0.2%, CaO 3-8%, MgO 1-3%, K2O 3-6%, Na2O 1-4%, P2O5 0.1-0.3%, SrO 4-6%, ZrO2 0.01-0.05%, BaO 3-5%, ZnO 5-10%, PbO 0.02-0.06%, and loss on ignition 0.2-0.5%.
9. A method for preparing a ceramic rock plate according to any one of claims 1 to 8, characterized in that: The following steps are involved: The first glaze, the second glaze, the spray-printed pattern and the protective glaze are sequentially applied on the blank to form the first glaze layer, the second glaze layer, the pattern layer and the protective glaze layer in sequence. After drying, the blank is fired in a kiln to obtain the ceramic rock slab.
10. The method for preparing a ceramic rock plate according to claim 9, characterized in that: The maximum sintering temperature is 1200-1220° C.; and / or the sintering period is 40-60 minutes.
Citation Information
Patent Citations
Blank for manufacturing bakeware ceramic products, and corresponding glaze and manufactured products thereof
CN101348362A
Outer-wall insulated coating with nano silicate fillers and preparation method of outer-wall insulated coating
CN104212289A
Heat-reflecting lightweight ceramic tile as well as preparation method and application thereof
CN115385725A
Ceramic rock plate with skin texture and preparation method and application thereof
CN117736019A
Ceramics, method for manufacturing ceramics, ceramic production granule and production method thereof
JP2021169394A